2D organ-like molybdenum carbide (MXene) coupled with MoS2 nanoflowers enhances the catalytic activity in the hydrogen evolution reaction. Issue 8 (5th February 2020) - Ren, Jie; Zong, Hui; Sun, Yuyun; Gong, Shijing; Feng, Yu; Wang, Zhenguo; Hu, Le; Yu, Ke; Zhu, Ziqiang
Abstract : Our work introduces an emerging route for the synthesis of MoS2 nanoflowers decorating organ-like Mo2 CT x MXene. This effective synthesis strategy of MoS2 @Mo2 CT x nanohybrid structure can shed some light on energy-related applications. Abstract : Two-dimensional molybdenum carbides belong to a novel family of 2D transition metal carbides/nitrides called MXenes, which have a wide range of electrochemical applications. However, the synergistic catalysis of transition metal carbides and disulfides has not been studied in depth. A strategy was proposed to prepare a 2D organ-like Mo2 C MXene matrix derived from Mo2 Ga2 C crystals, coupled with MoS2 nanoflowers to explore the hydrogen evolution reaction (HER) of molybdenum carbides and disulfides. Compared with Mo2 CT x (where T x means F, O, and OH surface terminations) Mxene catalysts, MoS2 @Mo2 CT x nanohybrids showed significantly enhanced HER activity, with a low overpotential of 176 mV in alkaline media at a current density of 10 mA cm −2 and a very small overpotential of 26 Ω. Density functional theory calculations indicated that the reduction of the hydrogen adsorption energy of the MoS2 @Mo2 CT x nanohybrids could be attributed to fast electron transport ensured by Mo2 CT x with intrinsic conductivity and a large number of hydrogen adsorption sites provided by MoS2 nanoflowers. The synthetic method is promising to tailor the specific properties by preparing organ-like molybdenum carbides coupled with MoS2 nanoflowers.